NONLINEAR FINITE ELEMENT ANALYSIS OF PRESTRESSED CONCRETE MEMBERS - Fahmi, Hani M.; Al-Bayati, Zubaidah A. (Nahrain University College of Engineering Journal, 2008)
A finite element method of analysis is used to study the strength and behavior of prestressed concrete members under short-term and sustainedload conditions. The degenerated assumed strain eight-node shell finite element is used with each node having five degrees of freedom. Material nonlinearity has been included in the analysis. Concrete is considered as an elastic-plastic material in compression with strain hardening. prestressing tendons are modeled by a multi-linear five branches stress-strain relationship. The layered approach is used to represent the concrete whereas the prestressing tendons are modeled as axial members embedded within the concrete elements. A computer program is developed and used for the analysis of prestressed concrete membershaving arbitrary tendon layout in either pretensioned or post-tensioned tendons. The tendon layout is specified and the loading due to prestressing is numerically calculated using the computer program. The validity of the proposed model for embedded bar representation of the prestressing tendons and the developed method of prestressing force inclusion into the entire member is demonstrated. The capabilities of the computer program resulting from the present developments are verified by analyzing experimentally tested prestressed concrete slabs. The computed results are compared with the available experimentaldata. The comparison verified the accuracy and adequacy of the method and models used utilizing the developed computer program.